Wireless-sensor-networks-based localization system for tracking positions in indoor systems - Dutta, Anindya. (2010)
In this project, we aim to develop localization and tracking system which can be used in an indoor environment. Accurate indoor localization has been an objective of the computing research community for a long time, and numerous indoor localization solutions based on 802.11, Bluetooth, ultrasound and infrared technologies have been considered. This project aims to develop indoor localization system based on wireless sensor networks (WSN). A WSN consists of spatially distributed autonomous sensor nodes which typically cooperatively monitor physical or environmental conditions over a geographical area. The Received Signal Strength Indicaor (RSSI) value of the packets distributed in such a network can be used to extrapolate the distances which the signals are travelling. This can then be utilised to develop and solve localisation algorithms. This in turn can enable the location tracking of a sensor in a given geographical area.